2020
DOI: 10.1038/s41598-020-77215-7
|View full text |Cite
|
Sign up to set email alerts
|

Brassica oleracea var. acephala (kale) improvement by biological activity of root endophytic fungi

Abstract: Brassica oleracea var. acephala (kale) is a cruciferous vegetable widely cultivated for its leaves and flower buds in Atlantic Europe and the Mediterranean area, being a food of great interest as a "superfood" today. Little has been studied about the diversity of endophytic fungi in the Brassica genus, and there are no studies regarding kale. In this study, we made a survey of the diversity of endophytic fungi present in the roots of six different Galician kale local populations. In addition, we investigated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 66 publications
(66 reference statements)
3
34
0
Order By: Relevance
“…Many studies have shown that the colonization of ECMF and DSE could confer pathogen resistance to host plants (Mandyam and Jumpponen, 2005;Zhang and Tang, 2012;Zhang et al, 2017;Chu et al, 2019;Poveda et al, 2020), and this effect was observed in the present study, as well. Exogenous inoculation with ECMF/DSE delayed the development of PWD symptoms and reduced disease severity of P. tabulaeformis (Figure 1).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Many studies have shown that the colonization of ECMF and DSE could confer pathogen resistance to host plants (Mandyam and Jumpponen, 2005;Zhang and Tang, 2012;Zhang et al, 2017;Chu et al, 2019;Poveda et al, 2020), and this effect was observed in the present study, as well. Exogenous inoculation with ECMF/DSE delayed the development of PWD symptoms and reduced disease severity of P. tabulaeformis (Figure 1).…”
Section: Discussionsupporting
confidence: 84%
“…They colonize the epidermis and cortex of plant roots inter-and intra-cellularly and form characteristic structures of melanized hyphae and microsclerotia (Mandyam and Jumpponen, 2005). Poveda et al (2020) found that Brassica oleracea var. acephala (kale) root endophytes were able to activate a systemic resistance in the plant against the bacterial pathogen Xanthomonas campestris and confer resistance against Mamestra brassicae larvae.…”
Section: Introductionmentioning
confidence: 99%
“…The rhizosphere offers varieties of carbon-rich micro-habitats, and beneficial microorganism populations can colonize by using such substrates (Caracciolo and Terenzi, 2021). Plants contribute to the assemblage of their rhizobiome (Mercado-Blanco et al, 2018;Sasse et al, 2018;Poveda et al, 2020), and some plant species can have their specific microbial community (Mhlongo et al, 2018), which can, in turn, change during their growing stage, and in different root regions, the results of the LZ(CX) rhizosphere fungal communities tending to be similar in this study are consistent with this view. The composition of root exudates may be different and lead to differences in rhizosphere microbial populations, depending on plant species, growth phases, exposure of a plant to stress conditions, and, sometimes, differences in plants of the same species (Sasse et al, 2018;Zhalnina et al, 2018;Caracciolo and Terenzi, 2021).…”
Section: Rhizosphere Microbiome Assembly Results From the Combination Of Microbial Substrate-utilization Traits And Plant-root Exudationsupporting
confidence: 85%
“…The increased abundance of several soil fungal groups noted in intercropping plots in this study, such as Edenia and Clonostachys species, is particularly noteworthy in this context. Species belonging to these genera are associated with increased plant health, biocontrol of plant diseases and increased resistance against herbivore damage on plants (Iqbal et al 2018;Macías-Rubalcava et al 2008;Poveda et al 2020).…”
Section: Discussionmentioning
confidence: 99%